If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + 4 = 2u + -9 Reorder the terms: 4 + 3u = 2u + -9 Reorder the terms: 4 + 3u = -9 + 2u Solving 4 + 3u = -9 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 4 + 3u + -2u = -9 + 2u + -2u Combine like terms: 3u + -2u = 1u 4 + 1u = -9 + 2u + -2u Combine like terms: 2u + -2u = 0 4 + 1u = -9 + 0 4 + 1u = -9 Add '-4' to each side of the equation. 4 + -4 + 1u = -9 + -4 Combine like terms: 4 + -4 = 0 0 + 1u = -9 + -4 1u = -9 + -4 Combine like terms: -9 + -4 = -13 1u = -13 Divide each side by '1'. u = -13 Simplifying u = -13
| 20x+15=30x+10 | | 4(d+3)+2=10 | | 3(d-12)=d+24 | | 9b+10=1 | | 2p+8=6 | | 3x+26=x+4 | | 20+8=6 | | 2x-4x^2= | | 16-3t=-7t | | 18-5(x+1)=3(x-1) | | 10g-47-4g=16+3g | | 8x^3-6x+1=0 | | 22-4x=2x-4 | | w-5+3w=6w-1 | | 10c+5=4c-1 | | 3x+3=4x-6 | | 7(x-10)=21 | | 14*(2x+2)=1716+6*(x+2) | | x^2+6x+8=e^2 | | z^2+iz=0 | | 3.3x=6.5(10x+4) | | ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= | | 7x+5=45+3x | | ln(x)+ln(x-3)=ln(40) | | 6(p-5)-(4p+9)=25 | | 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 | | 2x^2+3x=200 |